Magnetic susceptibility in the prediction of soil attributes in southern Brazil - Ramos, Priscila Vogelei; Inda, Alberto Vasconcellos; Barron, Vidal; Teixeira, Daniel De Bortoli; Marques, Jose [UNESP] (Wiley-Blackwell, 2021)
Global demand for soil information has led to investigations that have adopted ways to estimate soil attributes quickly and effectively. In this context, magnetic susceptibility (chi) has gained prominence because it is a technique capable of estimating other attributes that are more difficult to acquire. This study aimed to (a) evaluate the performance of chi for the prediction of sand, silt, clay, hue, hematite/(hematite + goethite) ratio, Fe content of pedogenic iron oxides, and remaining phosphorus and (b) develop maps of chi, soil attributes and attributes predicted by chi in the state of Rio Grande do Sul (RS), Brazil. Here, 198 soil samples under forest and native pasture were used for testing the potential of chi as a predictive technique, separating the data into calibration (n(c) = 149) and validation sets (n(v) = 49). Linear regression was used to obtain the pedotransfer equations according to soil classes and lithology. To visualize the distribution of the values of chi and other soil attributes in RS, maps were made with the real values of chi and the real and estimated values of soil attributes. The great range of the chi values and related attributes was associated with the lithological and pedological influence, allowing the construction of predictive models that encompass a large gradient of chi. In the predictions made in groups, the attributes of Oxisols and Ultisols were best estimated by chi; however, among the lithology groups, the extrusive igneous rocks stood out.